Acute oral toxicity test and determination of lethal dose (LD50) of Garcinia forbesii King leaf extract in wistar rats - Rudiansyah, Mohammad; Rosida, Azma; Kania, Nia; Devi, Wivina Riza; Nirmalasari, Nila (Pharmaciana, 2025)
Garcinia forbesii King, an endemic plant from Sumatra and Kalimantan, is traditionally used for treating skin infections and inflammation. Its potential use as a raw material for medicines needs to be supported by safety tests. The purpose of this study is to assess the acute toxicity of its 70% leaf extract in male Wistar rats, evaluating clinical symptoms, body weight changes, organ indices, and the lethal dose (LD50). The study administered extract doses orally at 5 (G2), 50 (G3), 300 (G4), and 2,000 (G5) mg/kg BW, monitoring toxicity signs over 14 days. Symptoms such as piloerection, respiratory distress, and soft feces were noted. Significant weight loss was observed at doses of 2,000 mg/kg BW. There was no significant effect on the kidney index, but the liver and heart indices exhibited significantly lower changes compared to the control. The LD50 value was estimated to be between 2,000-5,000 mg/kg BW. Further studies are recommended to assess histopathological effects and identify harmful chemicals in the plant.